Changing relationships between HIV prevalence and circumcision in Lesotho - Michel Garenne (My University, 2023)
The study investigates the complex relationships between circumcision and HIV prevalence in Lesotho, using Demographic and Health surveys (DHS) conducted in 2004, 2009 and 2014. Before the HIV epidemic, about half of the male adult population was circumcised as part of a traditional custom, and this proportion increased markedly after 2008 with the campaigns of Voluntary Medical Male Circumcision (VMMC), while HIV prevalence stayed at the same level. In 2004, HIV prevalence was higher in circumcised groups than in intact groups (RR=1.49, 95% CI=1.20-1.86). This relationship changed over time, and was inversed in 2014 (RR=0.86; 95% CI=0.70-1.06). The changing relationship seems to be due to an interaction with education, with more educated men being more circumcised and having less HIV over time. A multivariate analysis showed no net effect of circumcision on HIV, after controlling for wealth, education, and indicators of marriage and sexual behaviour. A small net effect of VMMC was found, probably due to condom use. In couple studies, the effect of circumcision and VMMC on HIV was not significant, with similar transmission from female to male and male to female. The study questions the amount of effort and money spent on VMMC in Lesotho.
Keywords: HIV/AIDS: Circumcision; Lesotho